Effects of Perceived Organizational Support and Commitment on Employee Performance via Organizational Citizenship Behavior - Lisa Andriani; Sunardi Sunardi; Sina Setyadi (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the mediating role of Organizational Citizenship Behavior (OCB) in the relationship between Perceived Organizational Support (POS), Perceived Organizational Commitment (POC), and employee performance in a state-owned enterprise in Indonesia. In the context of growing public expectations for improved service quality, organizations are challenged to enhance employee performance not only in formal roles but also in discretionary behaviors. Based on Social Exchange Theory (SET), this research proposes that POS and POC can affect performance both directly and indirectly through OCB. Data were collected through a census of 138 permanent employees at PT Jasa Raharja, East Java Branch. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships. The findings show that POS has a significant positive influence on both OCB and employee performance. On the other hand, POC significantly influences OCB but does not have a direct impact on performance. The results also reveal that OCB plays a partial mediating role in the relationship between POS and performance, while it acts as a full mediator in the relationship between POC and performance. These findings emphasize the importance of fostering OCB within the organization to optimize the impact of support and commitment on employee performance. Encouraging voluntary, extra-role behaviors can bridge the gap between how employees perceive organizational treatment and how they perform. The study suggests practical implications for human resource management in public sector institutions. Policies should focus on building a supportive and engaging work climate that enhances affective commitment and acknowledges employee contributions beyond formal duties. Doing so will not only improve individual performance but also contribute to broader organizational effectiveness in a competitive and service-oriented environment.